Not-Defect:The Mature Discipline of Testing. - Armour, Phillip G. (Communications of the ACM, 2004)
This article focuses on the development and testing of computer software. Almost all stages of software development focus on building things. Even the requirements gathering stages quickly segue into requirements specification writing stages. This is not a fault of the requirements stage per se, it is simply a subset of the whole product production paradigm. Testing as a directed activity is the only part of software development that has truly adopted the mind-set that one's job is not to catalog what one knows, it is to discover what we don't know. Most testing organizations understand and appreciate that their job is to intentionally find defects. There are always two stages in testing: exposing a bug, and fixing a bug. Interestingly, testing is also the area where most truly executable software is used in the development activity. The earlier specification, design, and code stages typically use word processors or similar applications for the bulk of their computer support. In the book "The Art of Software Testing," Glenford Myers asserts that the most important considerations in software testing are issues of economics and human psychology.